2020
DOI: 10.1093/mnras/staa062
|View full text |Cite
|
Sign up to set email alerts
|

Ionized gas outflow signatures in SDSS-IV MaNGA active galactic nuclei

Abstract: The prevalence of outflow and feedback signatures in active galactic nuclei (AGN) is a major unresolved question which large integral field unit (IFU) surveys now allow to address. In this paper, we present a kinematic analysis of the ionised gas in 2778 galaxies at z ∼ 0.05 observed by SDSS-IV MaNGA. Specifically, we measure the kinematics of the [OIII] λ5007Å emission line in each spatial element and fit multiple Gaussian components to account for possible non-gravitational motions of gas. Comparing the kine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 99 publications
6
86
1
Order By: Relevance
“…C1 and C2) indicate that the presence of outflows not only along the ionization axis, but also in locations away from it. Values of 80 500 km s −1 are commonly interpreted as tracers of AGN outflows (Zakamska & Greene 2014;Kakkad et al 2020;Wylezalek et al 2020). For Mrk 79, the highest 80 values are observed perpendicular to the AGN ionization axis, which is indicated as a continuous line in the 80 map of Fig.…”
Section: Discussionmentioning
confidence: 95%
“…C1 and C2) indicate that the presence of outflows not only along the ionization axis, but also in locations away from it. Values of 80 500 km s −1 are commonly interpreted as tracers of AGN outflows (Zakamska & Greene 2014;Kakkad et al 2020;Wylezalek et al 2020). For Mrk 79, the highest 80 values are observed perpendicular to the AGN ionization axis, which is indicated as a continuous line in the 80 map of Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Harrison et al 2016) and is a conservative estimate when compared to the cuts used in other works (e.g. 500 km s −1 in Wylezalek et al 2020).…”
Section: Modelling the Integrated Spectrummentioning
confidence: 85%
“…The KASHz sample is matched in redshift (z ∼ 2.0-2.5) to the SUPER sample. For comparison, we also plotted the w 80 distribution of low-redshift massmatched sample of MANGA galaxies from Wylezalek et al (2020), which is shown in blue in Fig. 3.…”
Section: Modelling the Integrated Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of z < 1 AGN from SDSS (e.g. Mullaney et al 2013;Woo et al 2016) and MaNGA (Wylezalek et al 2020) have shown that ionised outflows are ubiquitous, that their fraction is higher in AGN than in inactive galaxies and that it increases with AGN luminosity and/or Eddington ratio. Despite their widespread presence, their global effect on SFR in the host does not seem to be significant (e.g.…”
Section: Outflows From High To Low Redshiftmentioning
confidence: 99%